Accompaniment in Determining the Cost of Goods Sold (COGS) And Product Branding at D'zegerrr As a Micro Small and Medium Enterprise - Sari, Rika Puspita; Shanty, Ratna Nur Tiara; Prayudanti, Adhania Andika (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This study aims to assist the MSME "D'Zegerrr" in improving their Cost of Goods Sold (COGS) determination, product branding, and social media optimization. Established during the Covid-19 pandemic, "D'Zegerrr" produces traditional herbal drinks but faces challenges in accurately calculating COGS and creating a strong brand presence. Method: Analyzing current production costs, refining the COGS calculation using the Full Variable Costing method, improving product branding with a suitable slogan and packaging, and optimizing social media usage. Practical Applications: Practical applications of the study include helping the business better understand cost components, enhance brand identity, and increase engagement on social media platforms. Conclusion: The results show that by recalculating the COGS, "D'Zegerrr" can price their products more accurately, ensuring a fair profit margin. Additionally, the adoption of the slogan "Your health comes first" and the use of social media for brand promotion have increased customer awareness, positioning the MSME for greater market success.